An ANALYSIS OF STUDENTS’ DIFFICULTIES FACTOR IN READING SKILL AT SMPN LEMBANG BOSANG 12 KEPULAUAN SELAYAR - Yusrizal; Sangkala, Ismail; Ariana (FKIP Unismuh Makassar, 2025)
This research only focuses on analyzing students' difficulties in reading skills. Based on preliminary research, it shows that students still face difficulties in reading skills related to aspects and factors of reading skills. Therefore, this research aims to analyze students' difficulties in reading skills in Class IX of SMPN Lembang Bosang 12 Selayar Islands in the 2023/2024 academic year. descriptive qualitative research design was used in this research. Class IX was taken as a sample because it had lower reading scores than other classes.Document analysis, and interviews were used to collect data. The three main phases of data analysis are data condensation, data presentation, and conclusion drawing.After analyzing the data, the results showed that there were 3 aspects of students' difficulties in reading skills. Thus, the most difficult aspect that students face in reading skills is vocabulary. Based on student interviews, there are three factors of difficulty in reading skills. Thus, the factors of difficulty faced by students in reading skills are that students experience difficulty in understanding reading in long sentences, difficulty in using strategies, and difficulty in concentrating